DETERMINANT OF HEALTH PREVENTION OF DENGUE HEMORRHAGIC FEVER - Kwureh, Hendrikus Nara (Krafon Publishing, 2019)
Introduction: Dengue hemorrhagic fever (DHF) is one of the infectious diseases transmitted by mosquito bites that are found in tropical and subtropical areas around the world. The high cases of dengue fever show a lack of prevention efforts against dengue hemorrhagic fever. The purpose of this research is to know the factors related to dengue fever prevention efforts (DHF) in Kapuas Kanan Hulu Village Working Area of Durian River Community Health Center in 2018. Methods: This research method is quantitative with a cross sectional approach. The sampling technique uses Sample Random Sampling. The sample used was 97 families. Results: The results showed that there was a correlation between education and prevention of DHF in Kelurahan Kapuas Kanan Hulu Sintang District in 2018 (p=0.012. OR=3,150), there is correlation between knowledge with prevention effort of DHF in Kelurahan Kapuas Kanan Hulu Kabupaten Sintang 2018 (p=0,025. OR=2,786), there is correlation between attitude and prevention of DHF in Kelurahan Kapuas Kanan Hulu Kabupaten Sintang 2018 (p=0,007. OR=3,411), There is no correlation between information media with prevention effort of DHF in Kelurahan Kapuas Kanan Hulu Kabupaten Sintang 2018 (p=0,907. OR=0,877), There is correlation between health officer support and prevention effort of DHF in Kelurahan Kapuas Kanan Hulu Kabupaten Sintang 2018 (p=0,004. OR=3,700).